2020
DOI: 10.3390/molecules25173818
|View full text |Cite
|
Sign up to set email alerts
|

Varietal and Geographical Discrimination of Greek Monovarietal Extra Virgin Olive Oils Based on Squalene, Tocopherol, and Fatty Acid Composition

Abstract: Extra virgin olive oil (EVOO) is an important component of the Mediterranean diet and a highly priced product. Despite the strict legislation to protect it from fraudulent practices, there is an increasing demand to characterize EVOOs and evaluate their authenticity. For this purpose, 68 monovarietal EVOOs, originating from three regions of Greece (Peloponnese, Crete, and Lesvos) and two local cultivars (Koroneiki and Kolovi), were obtained during the harvesting period of 2018–2019. Fatty acids, squalene, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 45 publications
4
21
2
6
Order By: Relevance
“…Instead, Koroneiki cultivar is the most widespread all over the Greece, and the most well-known Greek olive cultivar. It is cultivated in many areas of the country, mainly in Peloponnese, Crete, and in the northwestern part of country [ 38 , 71 ]. Regarding Lianolia Kerkyras, this cultivar is mainly cultivated in the Ionian Islands and in the geographical region of Epirus.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, Koroneiki cultivar is the most widespread all over the Greece, and the most well-known Greek olive cultivar. It is cultivated in many areas of the country, mainly in Peloponnese, Crete, and in the northwestern part of country [ 38 , 71 ]. Regarding Lianolia Kerkyras, this cultivar is mainly cultivated in the Ionian Islands and in the geographical region of Epirus.…”
Section: Resultsmentioning
confidence: 99%
“…5.0–7.0% and 0.55–0.76%, respectively). Mikrou et al [ 36 ] studied 68 monovarietal EVOOs, originating from three regions of Greece and two local cultivars (Koroneiki and Kolovi), and reported similar concentration oleic, linoleic, and α -linolenic acid. The exception was the cultivar Kolovi, which had a higher linoleic acid content of 11.63% [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mikrou et al [ 36 ] studied 68 monovarietal EVOOs, originating from three regions of Greece and two local cultivars (Koroneiki and Kolovi), and reported similar concentration oleic, linoleic, and α -linolenic acid. The exception was the cultivar Kolovi, which had a higher linoleic acid content of 11.63% [ 36 ]. Other studies showed that Italian and Spanish olive oils had even lower values of C18 : 3, i.e., 0.49–0.54% [ 37 ] and 0.48% [ 38 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical research carried out on O. europaea has led to the isolation of several compounds cited above as well as a few other types of secondary metabolites which are present in almost all parts of the olive tree [1,[195][196][197][198]. The therapeutic utilities of O. europaea indicate its use in traditional medicine as well.…”
Section: Hydrocarbons and Sterolsmentioning
confidence: 99%